ChemInform Abstract: Combining Organocatalysis with Central‐to‐Axial Chirality Conversion: Atroposelective Hantzsch‐Type Synthesis of 4‐Arylpyridines. Issue 22 (12th May 2016) - Quinonero, Ophelie; Jean, Marion; Vanthuyne, Nicolas; Roussel, Christian; Bonne, Damien; Constantieux, Thierry; Bressy, Cyril; Bugaut, Xavier; Rodriguez, Jean
Abstract: Organocatalytic enantioselective Michael addition provides 4‐aryl‐1, 4‐dihydropyridines.